High-Power Laser Cutting of Steel Plates: Heat Affected Zone Analysis - Imed Miraoui; Mohamed Boujelbene; Mouna Zaied (Advances in Materials Science and Engineering)
The thermal effect of CO2 high-power laser cutting on cut surface of steel plates is investigated. The effect of the input laser cutting parameters on the melted zone depth (MZ), the heat affected zone depth (HAZ), and the microhardness beneath the cut surface is analyzed. A mathematical model is developed to relate the output process parameters to the input laser cutting parameters. Three input process parameters such as laser beam diameter, cutting speed, and laser power are investigated. Mathematical models for the melted zone and the heat affected zone depth are developed by using design of experiment approach (DOE). The results indicate that the input laser cutting parameters have major effect on melted zone, heat affected zone, and microhardness beneath cut surface. The MZ depth, the HAZ depth, and the microhardness beneath cut surface increase as laser power increases, but they decrease with increasing cutting speed. Laser beam diameter has a negligible effect on HAZ depth but it has a remarkable effect on MZ depth and HAZ microhardness. The melted zone depth and the heat affected zone depth can be reduced by increasing laser cutting speed and decreasing laser power and laser beam diameter.